The Bugis Siri’ Paradigm in a Collection of Short Stories Fighting in a Sarong By Alfian Dippahatang (Study Of Sosiology Literature) - Arnianti Parnisiska; Muhammad Saleh; Suarni Syam Saguni (HUMAN: South Asian Journal of Social Studies, 2021)
The study aims describe a character’s view of siri’s social conflict in a group of fighting in the sarong by Alfian Dippahatang. The research is is qualitative in description. The research source of the text, sentences, and pharagraphs embodies a person’s view of siri’ social conflict. The data source in the research is short stories Ustaz To Balo, Bukan Sayid, Ayahku memang Setan dan Bertarung dalam Sarung. The techniques used to analyze data of filtering, checking, presentation and drawing conclusions match the theory of literary sociology Ian Watt. Research shows that research shows that: the characters in the short story are described as developing a dim view of siri’s social conflict. of child, the Santri, Bulu Pao of community, Ranti, Patiasih, Sakir, Cenning, Bombang and Tarung has the view that the shame prevailing customary rules must be guarded by feelings of shame and fear which make them united masseddi siri’ is not instrling siri’ value pace causes other figures to feel ripakasiri’ or humiliated and the view of siri’ as an honor but ends up insulting each other is described by the author as something that tringgers conflict. Whears the leader to Balo, Habri and Bilang, had the view that siri’s main essence was in keeping dignity and honor. Siri’s a sure thing to Bugis play by society’s rules of action.Keyword: Social Conflict, Sociology Literature, Siri’, Short Stories Fighting In a Sarong; Alfian Dippahatang.